Design of a Savitzky-Golay Filter-Based vEMG-FES System - Ruikai Cao; Yixuan Sheng; Anqin Dong; Honghai Liu (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
It is evident that voluntary effort plays a crucial role in electrical stimulation rehabilitation, facilitating neuroplasticity enhancement in patients with neurological disorders. In this paper, we present a multichannel system designed for simultaneous functional electrical stimulation (FES) and volitional EMG (vEMG) acquisition using shared electrodes. The system employs hardware blanking with electrodes shorting to suppress stimulation artifacts and accelerate residual charge dissipation. Additionally, we adapt the Savitzky-Golay filter to extract high-quality, real-time vEMG from FES-contaminated signals, with the optimal filter parameters for different stimulation and blanking periods determined using a genetic algorithm and semi-synthesized signals. Simulation and experimental results confirm that the proposed system ensures robust and high-quality vEMG acquisition, even under varying parameters and across different individuals. In summary, this work advances the development of closed-loop rehabilitation applications and enables further investigation of neuromuscular characteristics under FES.